Associative Meaning Analysis in a Selected Song from The Rolling Stones - Astuti, Prihatin Puji; Antika, Ria (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This research titled "Associative Meaning Analysis in a Selected Song from The Rolling Stones" examines the presence and function of associative meaning in selected lyrics from the Rolling Stones’ recent works. The objective is to identify and analyze the types of associative meaning found in the lyrics. The study uses a qualitative descriptive approach with content analysis as the primary method. The data source consists of selected lyrical lines, which are analyzed using Leech’s (1985) theory of associative meaning. The analysis reveals six types of associative meaning: connotative, reflective, social, affective, collocative, and thematic. Connotative meaning adds emotional and symbolic depth, such as the phrase “sweet scents of Heaven,” which suggests peace beyond literal scent. Reflective meaning is observed in lyrics that express personal and collective emotions, including nostalgia and national pride mixed with disillusionment. Social meaning reflects cultural values embedded in the lyrics, while affective meaning evokes emotional responses such as joy and innocence, as seen in phrases like “the sweet sounds of children.” Collocative meaning is shown through word combinations like “Heaven” and “earth,” which carry spiritual associations. Thematic meaning is present in repeated contrasts, such as between the divine and the worldly, or between chaos and calm, giving unity to the overall message. These meanings are expressed through imagery, symbolism, and emotional variation, encouraging deeper engagement from listeners. In conclusion, the selected lyrics demonstrate how associative meaning is effectively employed to produce layered, meaningful messages. The use of associative meaning allows the Rolling Stones to connect with listeners on both emotional and intellectual levels.